Cortical plasticity in phantom limb pain: A fMRI study on the neural correlates of behavioral clinical manifestations. (30th October 2020) - Duarte, D.; Bauer, C.C.C.; Pinto, C.B.; Saleh Velez, F.G.; Estudillo-Guerra, M.A.; Pacheco-Barrios, K.; Gunduz, M.E.; Crandell, D.; Merabet, L.; Fregni, F.
Highlights: Novel task-based functional magnetic resonance imaging approach for phantom pain. Assess neural activation within motor, somatosensory and visual cortex. Activation in M1/S1 and shift in cortex representation not related to PLP. V1 activation is negatively correlated with PLP. Time since amputation and itching are potentially protective factors for PLP. Abstract: The neural mechanism of phantom limb pain (PLP) is related to the intense brain reorganization process implicating plasticity after deafferentation mostly in sensorimotor system. There is a limited understanding of the association between the sensorimotor system and PLP. We used a novel task-based functional magnetic resonance imaging (fMRI) approach to (1) assess neural activation within a-priori selected regions-of-interested (motor cortex [M1], somatosensory cortex [S1], and visual cortex [V1]), (2) quantify the cortical representation shift in the affected M1, and (3) correlate these changes with baseline clinical characteristics. In a sample of 18 participants, we found a significantly increased activity in M1 and S1 as well as a shift in motor cortex representation that was not related to PLP intensity. In an exploratory analyses (not corrected for multiple comparisons), they were directly correlated with time since amputation; and there was an association between increased activity in M1 with a lack of itching sensation and V1 activation was negatively correlated with PLP. Longer periods of amputation lead to compensatory changes in sensory-motor areas; and itching seems to be a protective marker for less signal changes. We confirmed that PLP intensity is not associated with signal changes in M1 and S1 but in V1.